Analysis of the Factors Influencing the Decision of Myanmar Students to Choose Finland for Higher Education - Phyo, Lwin (My University, 2025)
In recent years, Finland has emerged as an increasingly attractive destination for international students. Following the 2021 military coup in Myanmar, many students began seeking stable and secure environments for higher education. This study explores the central research question: What are the most influential push and pull factors for Myanmar students when choosing Finland for higher education? The research examines how political, financial, social and cultural shape this migration decision. To address this question, a mixed-methods approach was utilized, with emphasis on quantitative analysis. Data was collected through an online survey distributed over three weeks to Myanmar students currently studying in Finland, yielding 39 valid responses. Purposive and snowball sampling were used to reach this niche population. The findings revealed that major push factors include Myanmar’s political instability and lack of quality educational opportunities, while the pull factors include Finland’s reputation for safety, affordability, and high-quality education. Financial considerations, especially tuition affordability and cost of living significantly impacted decision making, with younger students showing pattern of reliance on family support. Social and cultural challenges, including language barriers and adaptation to Finnish society, were moderate but manageable through institutional support. The study provides practical implications for Finnish institutions and policymakers by emphasizing the financial, social and cultural needs of Myanmar students. It highlights the significance of targeted support services, and culturally inclusive integration programs to ease adaptation. However, this study is limited by the relatively small sample size and rely on self reported data, which may affect overall generalization. Furthermore, the high number of students enrolled in vocational pathways suggests the need for future research that more deeply examines the motivations and outcomes of vocational education among international students.
Keywords: studies abroad; international mobility; student exchange; Finland; mobility; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Systems Analytics